Welfare traits of cattle castrated immunologically and fed beta-adrenergic agonists - Luciane Silva Martello; Daniel Silva Antonelo; Nara Regina Brandão Cônsolo; Verônica Madeira Pacheco; João Alberto Negrão; Alessandra Fernandes Rosa; Paulo Roberto Leme; Rafael Vieira Sousa; Saulo da Luz Silva (Animal Bioscience, 2021)
Objective This work was carried out to evaluate the effects of zilpaterol hydrochloride (ZH) and ractopamine hydrochloride (RH) combined with immunocastration on the welfare traits of feedlot Nellore cattle. Methods Ninety-six Nellore males (average body weight [BW] = 409±50 kg; average 20 mo of age) were divided into two groups according to BW; half of the animals in each group received two doses of an immunocastration (ImC) vaccine in a 30 day interval, and the other half did not receive the vaccine (NoC). Afterward, the animals were housed and fed a common diet for 70 days. Then, they were split into three groups and fed one of the following diets for 30 additional days: control (CO) diet, with no β-AA; ZH diet, containing 80 mg/d ZH; and RH diet, containing 300 mg/d RH. Welfare traits were assessed by monitoring body surface temperature using infrared thermography (IRT) and plasma cortisol and temperament measurements. Results There was no interaction between sexual condition and diet for any trait. The ImC and NoC groups did not differ in rectal and ocular temperatures. The ImC animals had higher flight speeds (p = 0.022) and tended to have higher cortisol levels (p = 0.059) than the NoC animals. Animals fed ZH and RH did not differ in cortisol levels, respiratory rate, rectal temperature, temperature measured by IRT, or temperament behaviour. Conclusion The ImC animals showed a less stable temperament during handling practices than NoC, whereas ZH and RH supplementation had no adverse effects on animal welfare.